Penerapan teknologi virtual reality dalam sistem pembelajaran pendidikan tinggi di indonesia: Tantangan dan peluang - Ardhi, Muhammad Ali nur (Maliki Interdisciplinary Journal, 2025)
The use of Virtual Reality (VR) technology in education has garnered attention from academics and practitioners, especially in higher education. VR offers a more immersive and interactive learning experience, where students can engage with three-dimensional simulation environments. This article aims to analyze the implementation of VR technology in higher education learning systems in Indonesia, focusing on the challenges faced and the opportunities that can be leveraged. Through a literature review and data analysis from several universities, this study found that although VR has great potential in enhancing learning quality, there are major obstacles such as high costs, infrastructure limitations, and a lack of training for lecturers. However, with cooperation between the government, industry, and educational institutions, these challenges can be overcome, and VR can significantly contribute to improving students’ learning experiences.